Corrigendum to “Schizophrenia: a narrative review of etiological and diagnostic issues” (Consortium Psychiatricum, 2022, Volume 3, Issue 3, doi: 10.17816/CP132) - Sofia N. Oskolkova (Consortium Psychiatricum, 2023)
There is an error occurred in the article Schizophrenia: a narrative review of etiological and diagnostic issues published in the Consortium Psychiatricum journal (Volume 3 Issue 3) by Sofia Oskolkova. Due to a technical error on authors and editorial parts and without any malicious intent, the Errors in diagnostics of schizophrenia chapter links to incorrect references.